Pregnancy in granulomatous vasculitis. Issue 7 (July 1995) - Lima, F; Buchanan, N; Froes, L; Kerslake, S; Khamashta, M A; Hughes, G R
Abstract : OBJECTIVE–To study the fetal and maternal outcome of pregnancy in patients with granulomatous vasculitis. METHODS–Four pregnancies in two patients with Wegener's granulomatosis (WG) and one patient with Churg-Strauss syndrome (CSS) were identified and followed in our specialised clinic for pregnancy and connective tissue diseases. RESULTS–Three pregnancies ended with live babies and one with intrauterine death at 25 weeks of gestation. One WG patient remained in remission throughout pregnancy and the other experienced severe activity at 12 weeks. The CSS patient was in remission during her first pregnancy, but the disease flared severely in the second. CONCLUSIONS–Pregnancy in patients with granulomatous vasculitis requires preconceptual planning, careful clinical management, and vigorous treatment of active disease.